2013
DOI: 10.1371/journal.pone.0059437
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the Syndrome: Individual and Population Consistency in Behaviour in Rock Pool Prawn Palaemon elegans

Abstract: Animal personality has been widely documented across a range of species. The concept of personality is composed of individual behavioural consistency across time and between situations, and also behavioural trait correlations known as behavioural syndromes. Whilst many studies have now investigated the stability of individual personality traits, few have analysed the stability over time of entire behavioural syndromes. Here we present data from a behavioural study of rock pool prawns. We show that prawns are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Our results corroborate previous finding by Schoepf and Schradin (2012b) that showed male striped mice to be more socially investigative than females, which they interpreted as a willingness of males to more rapidly assess whether a stranger was a potential competitor or a mate. Taken together, our results indicate that there are important differences in the way personality is maintained within the sexes in striped mice, which could be related to differences between males and females in the costs and benefits of expressing a particular behaviour (Chapman et al 2013). Our findings that the personality of striped mice does not affect their social and reproductive tactics suggest that personality is unlikely to influence tactic switching and social systems, at least in species in which tactic switching follows a single strategy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our results corroborate previous finding by Schoepf and Schradin (2012b) that showed male striped mice to be more socially investigative than females, which they interpreted as a willingness of males to more rapidly assess whether a stranger was a potential competitor or a mate. Taken together, our results indicate that there are important differences in the way personality is maintained within the sexes in striped mice, which could be related to differences between males and females in the costs and benefits of expressing a particular behaviour (Chapman et al 2013). Our findings that the personality of striped mice does not affect their social and reproductive tactics suggest that personality is unlikely to influence tactic switching and social systems, at least in species in which tactic switching follows a single strategy.…”
Section: Discussionmentioning
confidence: 61%
“…Consistent individual differences may explain up to 30 % of the behavioural phenotypic variance within populations (Bell et al 2009;Chapman et al 2013). While most studies have measured the consistency of personality traits within a relatively short period of time of a few weeks (Chapman et al 2013), few long-term studies about personality have been conducted (Dammhan 2012;Herde and Eccard 2013;Montiglio et al 2014). Here, we showed that behavioural traits of individuals were consistent in the short (2 weeks) and long term (4-5 months), after one third of the lifespan of a striped mouse.…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted that there would be correlations between several key behavioural traits. Such behavioural syndromes have been seen in the rockpool prawn Palaemon elegans , where activity, exploration and boldness were correlated (Chapman, Hegg & Ljungberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between sexes in personality traits were assessed using Mann-Whitney U tests. The consistency of behaviour by sex was evaluated by comparing the values from the first set of assays with the second set using a Spearman's rank correlation test, as previously reported (Bell, et al, 2009;Chapman, Hegg, & Ljunberg, 2013;Herde & Eccard, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Differences between sexes in personality traits were assessed using Mann–Whitney U tests. The consistency of behaviour by sex was evaluated by comparing the values from the first set of assays with the second set using a Spearman's rank correlation test, as previously reported (Bell, et al, ; Chapman, Hegg, & Ljunberg, ; Herde & Eccard, ). To evaluate consistency over time, we compared the values of each behaviour measured in the first set of assays with the behaviours from the second set.…”
Section: Methodsmentioning
confidence: 99%